Stratification of papillary thyroid cancer relapse risk based on the results of molecular genetic studies - S. A. Lukyanov; S. V. Sergiyko; S. E. Titov; I. V. Reshetov; Yu. A. Veryaskina; A. V. Vazhenin; A. V. Gostimsky; L. I. Ippolitov; M. O. Rogova (Опухоли головы и шеи)
Introduction. Post-transcriptional mechanisms play a crucial role in the biological course and clinical manifestations of papillary thyroid cancer (PTC). Recent studies show that an increased content of oncogenic or reduced content of oncosuppressive microRNAs increases the aggressiveness of the tumor and correlates with an unfavorable prognosis of treatment, which allows them to be used in personalizing the treatment tactics of patients with PTC. The study objective is to compare the level of expression of 12 PTC-specific microRNAs and the frequency of V600E mutation of the BRAF gene in patients with different risk of relapse. Materials and methods. The study included 175 patients with PTC. For quantitative analysis of microRNA expression, a reverse transcription reaction followed by a real-time polymerase chain reaction in formalin-fixed paraffin blocks was used. Correlations between 12 microRNA expression and BRAF mutation with different clinical and anatomical features of PTC the risk of relapse according to the American Thyroid Association Risk Stratification System (2009) were analyzed. Results. We demonstrated that miR-146b, miR-221, miR-144, miR-451a, and miR-7 expression correlated with features such as extrathyroid tumor growth, larger size, multifocus, lymph node metastasis, and the presence of distant metastases of the PTC. Most importantly, miR-221, miR-144, miR-451a, and miR-7 expression correlated with risk levels, suggesting their potential significance in stratifying the risk of relapsing PTC. The dependence of the clinical behavior of PTC on the BRAF mutation has not been established.Conclusion. The result of the study will contribute to the individual choice of preoperative treatment tactics for patients with PTC.